PERLINDUNGAN KONSUMEN DALAM TRANSAKSI E-COMMERCE PERDAGANGAN INTERNASIONAL TINJAUAN DARI PERSPEKTIF HUKUM PERDATA INTERNASIONAL - Tusyadiah, Hafipah; Fitriani, Agnes; Sari, Desi Puspita; Maulana, Irfan (2024)
Consumer protection is a term used to describe the legal protection given to consumers in their efforts to meet their needs from things that could harm the consumers themselves.This research explains how consumers act in dealing with problems and also explains how legal protection is for consumers themselves. This research uses normative methods.Using a statutory approach, this research method focuses on analysis of legal norms, regulations, legal documents and legal principles related to consumer protection in international trade transactions. Parties such as consumers and sellers need to pay attention to the legal system of each country where the contract is made, which is adjusted to the rules of international law.